Treatment Options of Lemmel’s Syndrome: A Case of Benign Obstructive Jaundice in The Elderly - Abigail Prasetyaningtyas; Perdana Aditya Rahman; Aru Wisaksono Sudoyo; Achmad Fauzi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2015)
Lemmel’s syndrome, also known as duodenal diverticulum obstructive jaundice,  is a rare cause of benign obstructive jaundice that should be included in the differential diagnosis of biliary obstruction when PAD is present, in the absence of cholelithiasis or other detectable obstacle. Diagnosing Lemmel’s syndrome could be challenging, but being aware of this condition is important to avoid mismanagement and it begins with identification of PAD, while interpreting any bile duct imaging. It can be misinterpreted as periampullary tumors, biliary stones, or pancreatic pseudocyst. Symptomatic patients can be successfully managed endoscopically in many cases but surgical management would be necessary in selected cases.We present a patient with benign obstructive jaundice caused by Lemmel’s syndrome who was successfully treated with endoscopic sphicterectomy. A 67 years old female presented to the emergency department with chief complaint of jaundice. The patient was assesed to have obstructive jaundice cause by a duodenal mass, elevation of transaminase enzime supected caused by drug induced liver injury, hypertension (controlled), and anterior extensive coronary ischemia. Endoscopic retrograde cholangiopancreatografi (ERCP) showing mutiple giant diverticle in second part of duodenum, stenosis of the distal CBD with compression of diverticular extra luminal as a differential diagnosis. Endoscopic ultrasound (EUS) was performed to exlude a periampullary tumor, resulting distal CBD stenosis due to compression of multiple periampullary diverticula (PAD). We performed an endoscopic sphinterectomy (EST) and the stent was removed. A further evaluation of the tuberculous lymphadenitis was planned as outpatient setting. One month follow-up, no recurence of jaundice was observed.